Semi-purified fraction of Clinacanthus nutans induced apoptosis in human cervical cancer, SiHa cells via up-regulation of bax and down-regulation of Bcl-2 - Nik Aina Syazana Nik Zainuddin,; Hussin Muhammad,; Nik Fakhuruddin Nik Hassan,; Nor Hayati Othman,; Yusmazura Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cervical cancer is a leading cause of death in women, worldwide, and second in Malaysia. Nowadays, modern cancer treatment comes with negative and adverse side effects to the patients. Traditional medicinal plants such as Clinacanthus nutans has been locally recognized for its medicinal properties and was claimed for cancer treatment. According to our pilot study, a fraction of C. nutans has shown a potent inhibition on human cervical cancer cells, SiHa, in vitro. Hence, this study aimed to investigate the underlying anticancer mechanism of a semi-purified fraction (SF1) of C. nutans towards cervical cancer cells. Bioassay guided fractionation and further purification was carried out. All collected fractions of C. nutans were examined for cytotoxicity activity towards HeLa, SiHa and NIH cells by MTT Assay. SF1 exhibited better cytotoxic activity with best growth inhibition against SiHa cells (IC50 value = 9.60 μg/mL). Cytoselective effects were shown as no cytotoxicity observed in the treated normal NIH cells. SF1 induced early apoptosis event in SiHa cells as resulted by FITC-Annexin V/propidium iodide staining by flowcytometric analysis. The protein expression by flowcytometry using specific antibody conjugated fluorescent dye showed up-regulation of Bax and down-regulation Bcl-2 as well as increment of cytochrome C levels upon treatment with SF1. In conclusion, the findings suggested that SF1 demonstrated antiproliferative effects and induced apoptosis in SiHa cells through up-regulation of Bax and down-regulation of Bcl-2 via mitochondrial-dependent pathway.